Exercising Freedom over Time: Political and Cultural Implications - Alixon David Reyes Rodríguez (Universidad Nacional, Costa Rica, 2014)
The following paper addresses, in an essay format, the topic of the emergence of a culture that includes the redeeming recreation of important elements such as freedom and responsibility from a practical point of view, as a collective life project, consistent with humanitarian ideals and values. This is an analytical paper based on questions pertaining to categories and assumptions such as leisure time, work, and capitalism, among others. The objective of this analysis is the deconstruction of myths that, in the light of the theory and the political philosophies resulting from the industrial revolution, subsume recreation as an activity. Myths do not only do this but limit recreation to time specificity, thwarting the possibility of happiness and the liberation of consciousness from a dehumanizing and dehumanized ideology.